2022
DOI: 10.3389/fpubh.2022.904509
|View full text |Cite
|
Sign up to set email alerts
|

The associations between problematic smartphone use and blood pressure among 2,573 aged 9–17 years students in Shanghai, China

Abstract: ObjectivesThis study aimed to (1) examine the cross-sectional association between problematic smartphone use (PSU) and blood pressure (BP) in children and adolescents and (2) determine whether the association between PSU and BP differs by the grade of students.MethodsWe recruited a total of 2,573 participants from 14 schools in Shanghai by a two-stage sampling method. We derived BP data from the participant's most recent medical examination data, including systolic blood pressure (SBP) and diastolic blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Li et al [ 17 ] reported a prevalence of 12.26% of high blood pressure among students under 18 years old in Lanzhou. Liu et al [ 18 ] reported a prevalence of high blood pressure of 16.4% among students aged 7 to 17 in Sichuan Province. This study showed that the prevalence of high blood pressure among school students age 7 to 17 in Shenyang was 9.9%, which showed an upward trend compared to the national prevalence of 6.9% 10 years ago, [ 19 ] but was relatively low compared to other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 17 ] reported a prevalence of 12.26% of high blood pressure among students under 18 years old in Lanzhou. Liu et al [ 18 ] reported a prevalence of high blood pressure of 16.4% among students aged 7 to 17 in Sichuan Province. This study showed that the prevalence of high blood pressure among school students age 7 to 17 in Shenyang was 9.9%, which showed an upward trend compared to the national prevalence of 6.9% 10 years ago, [ 19 ] but was relatively low compared to other regions.…”
Section: Discussionmentioning
confidence: 99%